Physical inactivity among internally displaced persons in Nigeria - Olayinka Akinrolie; Ali Mamma Masta; Unyime S Jasper; Henrietta O Fawole; Ogochukwu Kelechi Onyeso; Omobolade Akinrolie; Ugochukwu Samuel Jumbo (Elsevier, 2022)
Background: Physical inactivity may complicate physical and mental health problems among internally displaced persons (IDPs). This study aimed to assess the prevalence of physical inactivity and its sociodemographic correlates among IDPs in Northeastern Nigeria. Methods: A total of 363 participants recruited from four IDP camps were categorized into physically inactive and active using International Physical Activity Questionnaire. Multiple logistic regression was used to explore the association between physical inactivity and sociodemographic correlates. Results: The prevalence of physical inactivity was 36.2%. Those who were males (Odd Ratio (OR) = 4.52, 95% Confidence Interval (CI) = 2.33 to 8.78) and Kanuri (OR = 2.53, 95% CI = 1.44 to 4.45) were more likely to be physically inactive. Younger participants were less likely to be physically inactive than those who were aged >49 years old. Conclusion: There is a high prevalence of physical inactivity among IDPs in Nigeria, and we found important sociodemographic factors associated with physical inactivity.